MON-559 Inappropriate Dosing of I-131 in Non-Metastatic Differentiated Thyroid Cancer - Alzenaidi, Ahlam (J Endocr Soc, 2019)
Differentiated thyroid cancer (DTC) accounts for the majority of thyroid cancers. While radioactive iodine (RAI) treatment after thyroidectomy plays an adjunctive role in some patients, the majority of patients with DTC at our institution receive RAI. The dosing of RAI is mostly empiric. A low dose of 30 mCi of I-131 is generally favored over higher doses in low or intermediate risk disease with lower risk features while higher doses may need to be considered for high risk patients (Haugen et al.). Higher rates of nausea, neck pain, lacrimal and salivary gland dysfunction and altered taste have been described for 100 mCi of I-131 compared with 30 mCi (Schlumberger et al. and Mallick et al.). The aim of this study was to determine the average dose of RAI for DTC and to identify the risk factors in low risk patients who received high dose of 131-I (≥100 mCi) at our tertiary care institution. Methods: This was a retrospective study of 33 patients with DTC who underwent RAI treatment from January 2015-May 2018 at a single academic medical center. Data were collected from the Nuclear Medicine department. Patients over the age of 18 with a documented non-metastatic DTC diagnosis were included. Patients who received RAI at an outside facility or with no pathology report were excluded. Results: Post-operative ultrasound was not routinely performed, and only 30% of patients had a neck US before RAI dose administration. The average dose of I-131 was 75.7 mCi regardless of the American Thyroid Association (ATA) risk. Sub-analysis per ATA risk group for the average dose showed 64.7 mCi in the low risk group, 98.9 mCi in the intermediate risk group, and 95.9 mCi in the high-risk group. The tertile ranges for the RAI dose were: T1: 29-33, T2:79-115 and T3:150 mCi. 63% of patients in the low risk group received a low dose of I-131(29-33m Ci), 22 % received 79-115 mCi and 13 % received 150 mCi. In the intermediate risk group 28% received 29-33 mCi and 28% received high dose 150 mCi while 42% received 79-115 mCi. In the high-risk ATA group 25% received a low dose of I-131with 29-33 mCi. Patients in the low risk group who received more than 30 mCi but less than 150 mCi showed no high-risk features with undetectable Tg level and no high risk histopathologic features or significant lymphadenopathy. However, of the patients in the low risk group who received ≥150 mCi, 75% had an elevated stimulated Tg level > 10 ng/ml and only one patient had a post-operative neck ultrasound that showed residual tissue. Conclusion: In this small cohort, patients with non-metastatic DTC received intermediate to high doses of RAI regardless of the ATA risk. More than 1/3 of patients in the low risk group received more than the recommended RAI dose per ATA guidelines. Despite the obvious multiple benefits of RAI post-operatively, selective criteria should be used to avoid unnecessary exposure of high dose RAI that may carry additional risk both in the short and long term.